Service Oriented Architecture and Business Process Management Two to Tango. - Pareek, Deepak
Today's business environment is changing rapidly. Business dynamics and technological innovations have left organizations with a disparate mix of operating systems, applications and databases-making it difficult, time consuming and costly for IT departments to deliver new applications that integrate heterogeneous technologies. The key to success in the networked economy is not only being able to create business processes to automate value chains, but also being able to modify these processes as business requirements change. Innovation in enterprise architecture will come from service oriented architecture (SOA) and business process management (BPM)